Streptococcus mutans Antibacterial Activity of 0.1% Lysozyme Tooth Paste as an Alternative for Children Below 3 Years Old in Preventing Early Childhood Caries (ECC) (Experimental Laboratory Study): Aktivitas Antibakteri Streptococcus mutans dari Pasta Gigi Lisozim 0,1% Sebagai Alternatif Untuk Anak Di Bawah 3 Tahun Dalam Mencegah Karies Anak Usia Dini (PAUD) (Studi Laboratorium Eksperimental) - Octiara, Essie; Sutadi, Heriandi; Siregar, Yahwardiah; Primasari, Ameta (TALENTA, 2021)
One of many possible ways of preventing Early Childhood Caries (ECC) is by removing tooth debris. Fluoride tooth paste usage by children under 3 years old must follow recommended quantity, because of its possibility of being ingested which then might cause fluorosis. Lysozyme as an active element in a toothpaste is able to mediate bacterial aggregation and inhibit bacterial adhesion and also activate bacterial autolysin by destructing bacterial cell wall. This study aimed to compared Streptococcus mutans antimicrobial activity of non-fluoride lysozyme toothpaste of various concentration such as 0.025, 0.05, 0.1, and 0.2 %. This was an experimental research with post test only design. The tested tooth paste was lysozyme-contained with 0.025, 0.05, 0.1 and 0.2% concentrations. Children tooth paste containing fluoride, enzyme tooth paste and 0.2% chlorhexidine became the positive control. Test of S. mutans antibacterial activity used 3 methods: disc diffusion, well, and microtiter plate method. Analytical test used Anova one way with Bonferoni post hoc and p<0.05 significant level. The results showed that all concentrations of lysozyme tooth paste had inhibitory effect on the growth of S. mutans (p<0.05). The highest mean of S. mutans antibacterial activity in lysozyme tooth paste were on 0.1 and 0.2% concentrations. Conclusion stated that 0.1% concentration of lysozyme tooth paste can be used as an alternative tooth paste for children under 3 years old